2006
DOI: 10.1002/j.2161-007x.2006.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for Counseling Adults With Terminal Illness: Personal and Professional Parallels

Abstract: This article presents a review of the literature on counseling adults with terminal illness, particularly the literature on the nature of preparation that counselors and other professionals who attend to the needs of adults with a terminal illness require. The authors review information and findings from philosophical, psychological, practical, and spiritual works. It is evident from these readings that a personal and professional examination of making meaning of life and death is integral to the performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Manis and Bodenhorn (2006) have also provided instructive guidelines for counselors preparing to work with patients with terminal illnesses that focus on the clinicians' own need to make meaning of illness and mortality. Kazarian (2001) has suggested that the incorporation of spirituality is particularly important in disease prevention and health promotion for African Americans, who are affected by cancer in disproportionate numbers in the U.S. population.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Manis and Bodenhorn (2006) have also provided instructive guidelines for counselors preparing to work with patients with terminal illnesses that focus on the clinicians' own need to make meaning of illness and mortality. Kazarian (2001) has suggested that the incorporation of spirituality is particularly important in disease prevention and health promotion for African Americans, who are affected by cancer in disproportionate numbers in the U.S. population.…”
Section: Implications For Practicementioning
confidence: 99%
“…Cole and Pargament (1999) have developed an intervention program, titled "Re-Creating Your Life: During and After Cancer," appropriate for patients with cancer who are "spirituality oriented" (p. 395), and others (Breitbart, Gibson, Poppito, & Berg, 2004;Gibson, Pessin, McLain, Shah, & Breitbart, 2004;Kristeller et al, 2005;Puchalski, Dorff, & Hendi, 2004) have offered similar intervention models. Manis and Bodenhorn (2006) have also provided instructive guidelines for counselors preparing to work with patients with terminal illnesses that focus on the clinicians' own need to make meaning of illness and mortality. Kazarian (2001) has suggested that the incorporation of spirituality is particularly important in disease prevention and health promotion for African Americans, who are affected by cancer in disproportionate numbers in the U.S. population.…”
Section: Implications For Practicementioning
confidence: 99%
“…For example, clinical trials of a meaning-centered group intervention, which was based on Frankl's ideas as well as listening to people who were dying, have demonstrated significant effects on the degree of sadness experienced by people with terminal cancer (see Greenstein & Breitbart, 2000). The counseling literature has reinforced the idea that counselors working with people facing EOL situations can learn from the experiences of, or provide assistance to, people who have faced death, are dying, or who have a chronic/terminal illness such as HIV (Buki, Kogan, Keen, & Uman, 2005;Burke & Miller, 1996;Freeman & Ward, 1998;Holt, Houg, & Romano, 1999;Ingersoll, 2000;Kinnier, Tribbensee, Rose, & Vaughan, 2001;Manis & Bodenhorn, 2006;O'Halloran & Altmaier, 1996;Shepherd Johnson, 2003;Springer & Lease, 2000;Vaughan & Kinnier, 1996).…”
Section: A9c Confidentialitymentioning
confidence: 99%
“…In fact, some authors argue that they should be emphasized alongside the biological, psychological, and social dimensions, creating a "biopsychosociospiritual" framework (Kaut, 2002(Kaut, , 2006Sulmasy, 2002). The counseling literature has included some discussion of the importance of spirituality when people are near the end of life (Buki et al, 2005;Burke & Miller, 1996;Holt et al, 1999;Ingersoll, 2000;Manis & Bodenhorn, 2006;Shepherd Johnson, 2003), but much more can and should be considered when people are dying, especially for members of diverse groups (e.g., Born, Greiner, Sylvia, Butler, & Ahluwalia, 2004;Puchalski, Dorff, & Hendi, 2004). As was discussed earlier, attention has been given to existential considerations, which can be placed under the broad heading of spirituality; in general, however, the discussion of religion and nonexistential spirituality has taken place in other literatures.…”
Section: A9c Confidentialitymentioning
confidence: 99%
“…Kübler-Ross has been credited for changing the way healthcare professionals, including therapists, view dying persons. Basically, she urged others to view death as natural, not as an illness (Manis & Bodenhorn, 2006).…”
Section: Historymentioning
confidence: 99%